To each its own: differential response of specialist and generalist herbivores to plant defence in willows - Volf, Martin; Hrcek, Jan; Julkunen-Tiitto, Riitta; Novotny, Vojtech (Journal of animal ecology, 2015)
Plant-insect food webs tend to be dominated by interactions resulting from diffuse co-evolution between plants and multiple lineages of herbivores rather than by reciprocal co-evolution and co-cladogenesis. Plants therefore require defence strategies effective against a broad range of herbivore species. In one extreme, plants could develop a single universal defence effective against all herbivorous insects, or tailor-made strategies for each herbivore species. The evolution and ecology of plant defence has to be studied with entire insect assemblages, rather than small subsets of pairwise interactions. The present study examines whether specialists and generalists in three coexisting insect lineages, forming the leaf-chewing guild, respond uniformly to plant phylogeny, secondary metabolites, nutrient content and mechanical antiherbivore defences of their hosts, thus permitting universal plant defence strategies against specialized and generalist folivorous insects from various taxa. The extensive data on folivorous assemblages comprising three insect orders and 193 species are linked with plant phylogeny, secondary chemistry (salicylates, flavonoids and tannins), leaf morphological traits [specific leaf area (SLA) and trichome coverage], nutrient (C : N) content and growth form of eight willow (Salix) and one aspen (Populus) species growing in sympatry. Generalists responded to overall host plant chemistry and trichomes, whilst specialists responded to host plant phylogeny and secondary metabolites that are unique to willows and that are capable of being utilized as an antipredator protection. We did not find any significant impact of other plant traits, that is SLA, C : N ratio, flavonoids, tannins and growth form, on the composition of leaf-chewing communities. Our results show that the response to plant traits is differential among specialists and generalists. This finding constrains the ability of plants to develop defensive traits universally effective against herbivores and may lead to diversification of plant defensive mechanisms into several complementary syndromes, required for effective protection against generalists and specialists from multiple insect taxa comprising most leaf-chewing assemblages. These results point to the necessity of broad studies of plant-herbivore interactions, across multiple insect taxa and guilds.
Keywords: Salix; fylogeneze; zvířata; salicylany; hmyz; býložravci; biologická evoluce; flavonoidy; Insecta; Flavonoids; Populus; Herbivory; Phylogeny; Tannins; Plant Leaves; Biological Evolution; taniny; Animals; listy rostlin; Salicylates